Hydrogenated nitrile rubber
Patent Information
- Application Number
- JP2024140958
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-30
- Filing Date
- 2024-08-22
- Publication Date
- 2025-03-14
Smart Images

Figure 2025036227000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a hydrogenated nitrile rubber and a method for producing the same, a veil made of hydrogenated nitrile rubber, and a binder for positive electrodes obtained by dispersing or dissolving hydrogenated nitrile rubber in a solvent. [Background technology]
[0002] Electrochemical devices such as lithium ion secondary batteries, lithium ion capacitors, and electric double layer capacitors are small, lightweight, have high energy density, and can be repeatedly charged and discharged, and are used in a wide range of applications. Therefore, in recent years, improvements in battery components such as electrodes have been studied in order to further improve the performance of electrochemical devices.
[0003] Here, an electrode used in an electrochemical element usually includes a current collector and an electrode mixture layer formed on the current collector. This electrode mixture layer is formed, for example, by applying a slurry containing an electrode active material, a conductive material, a binder, etc., onto the current collector and drying the applied slurry.
[0004] In recent years, therefore, attempts have been made to improve the binder used in forming the electrode mixture layer in order to achieve further improvements in the performance of electrochemical elements. For example, studies have been made on a technique of using a polymer containing a nitrile group-containing monomer unit as the binder (see, for example, Patent Documents 1 to 4). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2016 / 103730 [Patent Document 2] Patent No. 6870772 [Patent Document 3] Patent No. 6911985 [Patent Document 4] JP 2018-160421 A Summary of the Invention [Problem to be solved by the invention]
[0006] Here, the binder for the electrochemical element is required to have excellent stability of the conductive material dispersion liquid when an electrode for the electrochemical element is produced, and to remarkably increase the peel strength of the electrode. However, the above-mentioned conventional techniques have room for further improvement in these respects.
[0007] Therefore, an object of the present invention is to provide a hydrogenated nitrile rubber and a method for producing the same, which can increase the stability of a conductive material dispersion and remarkably improve the peel strength of the produced electrode.
[0008] Another object of the present invention is to provide a hydrogenated nitrile rubber veil which can enhance the stability of a conductive material dispersion and remarkably improve the peel strength of the produced electrode.
[0009] An object of the present invention is to provide a binder for a positive electrode that can enhance the stability of a conductive material dispersion and can significantly improve the peel strength of the produced electrode. [Means for solving the problem]
[0010] The present inventors have conducted extensive research in view of the above problems and have found that when hydrogenated nitrile rubber containing a nitrile group-containing monomer unit and a conjugated diene monomer unit and / or an alkylene structural unit and having an iodine value, weight average molecular weight and calcium (Ca) content within a specific range is used in the manufacture of an electrode, the stability of the conductive material dispersion is good and the peel strength of the electrode is significantly improved. In particular, it has been difficult to achieve a high level of balance between these two in the manufacture of conventional electrochemical elements, but it has been found that this can be achieved by combining the iodine value and calcium (Ca) content of the hydrogenated nitrile rubber within the characteristic ranges.
[0011] The present inventors have also found that the above properties can be further improved by including a specific antioxidant in the hydrogenated nitrile rubber or by limiting the palladium (Pd) content, the magnesium (Mg) content, or the sodium (Na) content.
[0012] The present inventors have also found that the above-mentioned properties can be significantly improved by increasing the bulk density of the hydrogenated nitrile rubber. This is believed to be because hydrogenated nitrile rubber with a high bulk density has almost no oxygen present therein, preventing the generation of oxygen radicals and improving various properties. They have also found that the synergistic effect with the phenol-based antioxidant is high, and the stability of the conductive material dispersion can be significantly improved.
[0013] The present inventors have also found that hydrogenated nitrile rubber obtained by using calcium chloride as a coagulant improves the dispersibility of a conductive material dispersion and the electrode peel strength of an electrochemical element such as a lithium ion secondary battery, and also suppresses cracking of the active material layer after a cycle test, thereby improving cycle characteristics.
[0014] The present inventors have found that hydrogenated nitrile rubber, which enhances the stability of a conductive material dispersion and the electrode peel strength, can be easily produced by coagulating an emulsion polymerization liquid obtained by emulsion polymerizing a monomer component containing a nitrile group-containing monomer and a conjugated diene monomer with calcium chloride, and then hydrogenating the resulting polymer with a rhodium-based catalyst and / or a ruthenium-based catalyst.
[0015] The present inventors further found that the effect of the present invention can be maintained by maintaining the hydrogenated nitrile rubber of the present invention in a baled state, and that dispersing or dissolving the hydrogenated nitrile rubber of the present invention in N-methylpyrrolidone provides a binder solution suitable for producing a positive electrode for an electrochemical element.
[0016] Based on these findings, the present inventors have completed the present invention.
[0017] Thus, according to the present invention, there is provided a hydrogenated nitrile rubber which contains a nitrile group-containing monomer unit and a conjugated diene monomer unit and / or an alkylene structural unit, and has an iodine value of 60 to 120 mg / 100 mg, a weight average molecular weight (Mw) in the range of 1,000 to 1,000,000, and a calcium (Ca) content in the range of 50 to 2,500 ppm.
[0018] The hydrogenated nitrile rubber of the present invention preferably further contains a phenol-based antioxidant, the content of which is preferably in the range of 0.001 to 2% by mass.
[0019] In the hydrogenated nitrile rubber of the present invention, the palladium (Pd) content is preferably 50 ppm or less.
[0020] In the hydrogenated nitrile rubber of the present invention, the magnesium (Mg) content is preferably 50 ppm or less.
[0021] In the hydrogenated nitrile rubber of the present invention, the sodium (Na) content is preferably 300 ppm or less.
[0022] In the hydrogenated nitrile rubber of the present invention, the bulk density is 0.8 g / cm 3 In the hydrogenated nitrile rubber, the total ratio of the nitrile group-containing monomer units and the conjugated diene monomer units and / or alkylene structural units in the hydrogenated nitrile rubber is preferably 95 mass% or more.
[0023] According to the present invention, there is also provided a method for producing the above-mentioned hydrogenated nitrile rubber, which comprises a step of emulsion-polymerizing a monomer component containing a nitrile group-containing monomer and a conjugated diene monomer, coagulating the polymer obtained by the polymerization with calcium chloride, and hydrogenating the polymer with a rhodium-based catalyst and / or a ruthenium-based catalyst.
[0024] In the method for producing hydrogenated nitrile rubber of the present invention, the hydrogenated nitrile rubber after the hydrogenation is preferably dried using a screw-type extruder.
[0025] In the method for producing hydrogenated nitrile rubber of the present invention, the screw-type extruder preferably has a reduced pressure drying barrel.
[0026] According to the present invention, there is also provided a hydrogenated nitrile rubber bale obtained by baling the above hydrogenated nitrile rubber.
[0027] According to the present invention, there is further provided a binder for a positive electrode, which is obtained by dispersing or dissolving the above hydrogenated nitrile rubber in N-methylpyrrolidone (NMP). Effect of the Invention
[0028] According to the present invention, there are provided a hydrogenated nitrile rubber which has excellent stability of a conductive material dispersion and can improve the peel strength of a produced electrode, a method for producing the same, a hydrogenated nitrile rubber veil made of hydrogenated nitrile rubber, and a binder for a positive electrode which is obtained by dispersing or dissolving hydrogenated nitrile rubber in a solvent. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0029] Hereinafter, an embodiment of the present invention will be described in detail.
[0030] The hydrogenated nitrile rubber of the present invention is characterized by comprising a nitrile group-containing monomer unit, a conjugated diene monomer unit and / or an alkylene structural unit, and having an iodine value of 60 to 120 mg / 100 mg, a weight average molecular weight (Mw) in the range of 1,000 to 1,000,000, and a calcium (Ca) content in the range of 50 to 2500 ppm.
[0031] <Monomer components> The hydrogenated nitrile rubber of the present invention contains a nitrile group-containing monomer unit and a conjugated diene monomer unit and / or an alkylene structural unit. The hydrogenated nitrile rubber is a component that can function as a binder that holds an electrode active material and the like from a current collector without causing the electrode active material to be detached from the current collector in an electrode mixture layer formed in an electrochemical element. The hydrogenated nitrile rubber can also function as a dispersant that can disperse a conductive material in a conductive material dispersion liquid that contains a conductive material.
[0032] Specifically, the hydrogenated nitrile rubber may be a hydrogenated polymer obtained by hydrogenating a polymer containing a conjugated diene monomer unit and a nitrile group-containing monomer unit, etc. Here, when the polymer containing the conjugated diene monomer unit and the nitrile group-containing monomer unit is completely hydrogenated, it becomes a polymer containing an alkylene structural unit and a nitrile group-containing monomer unit, and when the hydrogenation is partially performed, it becomes a polymer containing a conjugated diene monomer unit, an alkylene structural unit and a nitrile group-containing monomer unit.
[0033] (nitrile group-containing monomer unit) The nitrile group-containing monomer capable of forming the nitrile group-containing monomer unit may be an α,β-ethylenically unsaturated nitrile monomer. Specifically, the α,β-ethylenically unsaturated nitrile monomer is not particularly limited as long as it is an α,β-ethylenically unsaturated compound having a nitrile group, and examples thereof include acrylonitrile; α-halogenoacrylonitrile such as α-chloroacrylonitrile and α-bromoacrylonitrile; α-alkylacrylonitrile such as methacrylonitrile and α-ethylacrylonitrile; and the like. Among these, acrylonitrile is preferred. The nitrile group-containing monomer may be used alone or in combination of two or more kinds at any ratio.
[0034] The content ratio of the nitrile group-containing monomer unit in the hydrogenated nitrile rubber is preferably 10% by mass or more, more preferably 15% by mass or more, even more preferably 20% by mass or more, and preferably 50% by mass or less, more preferably 45% by mass or less, and even more preferably 40% by mass or less, based on 100% by mass of all repeating units in the hydrogenated nitrile rubber. If the content ratio of the nitrile group-containing monomer unit is within the above-mentioned range, the dispersion stability of the conductive material dispersion can be increased, and the peel strength of the obtained electrode can be further improved.
[0035] (Conjugated diene monomer units) Here, examples of the conjugated diene monomer capable of forming the conjugated diene monomer unit include conjugated diene compounds having 4 or more carbon atoms, such as 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 2-ethyl-1,3-butadiene, 1,3-pentadiene, etc. Among these, isoprene and 1,3-butadiene are preferred, and 1,3-butadiene is particularly preferred.
[0036] (Alkylene structural unit) Here, the alkylene structural unit has the general formula: -C n H 2n - [where n is an integer of 2 or more]. The alkylene structural unit may be linear or branched, but from the viewpoint of reducing the resistance of the electrode and improving the rate characteristics of the electrochemical device, the alkylene structural unit is preferably linear, i.e., a linear alkylene structural unit. The alkylene structural unit preferably has 4 or more carbon atoms (i.e., n in the above general formula is an integer of 4 or more).
[0037] The alkylene structural unit may be linear or branched, but is preferably linear, i.e., a linear alkylene structural unit. The alkylene structural unit preferably has 4 or more carbon atoms (i.e., n in the above general formula is an integer of 4 or more).
[0038] The method for introducing an alkylene structural unit into a polymer is not particularly limited, but may be, for example, the following method (1) or (2): (1) A method in which a polymer is prepared from a monomer composition containing a conjugated diene monomer, and the polymer is hydrogenated to convert the conjugated diene monomer unit into an alkylene structural unit. (2) A method for preparing a polymer from a monomer composition containing a 1-olefin monomer Among these, the method (1) is preferred because the polymer can be easily produced.
[0039] That is, the alkylene structural unit is preferably a structural unit obtained by hydrogenating a conjugated diene monomer unit (conjugated diene hydride unit), and more preferably a structural unit obtained by hydrogenating a 1,3-butadiene unit (1,3-butadiene hydride unit).
[0040] Examples of the 1-olefin monomer include ethylene, propylene, 1-butene, and 1-hexene.
[0041] These conjugated diene monomers and 1-olefin monomers can be used alone or in combination of two or more kinds.
[0042] The total content of the conjugated diene monomer units and the alkylene structural units in the hydrogenated nitrile rubber is preferably 50% by mass or more, more preferably 55% by mass or more, particularly preferably 60% by mass or more, and preferably 90% by mass or less, more preferably 85% by mass or less, particularly preferably 80% by mass or less, when the total repeating units in the polymer (the total of the structural units and the monomer units) is taken as 100% by mass. If the total content of the conjugated diene monomer units and the alkylene structural units in the polymer is within the above range, the dispersion stability of the conductive material dispersion and the cycle characteristics of the electrochemical element can be improved.
[0043] In addition, when the hydrogenated nitrile rubber has only either one of the content ratio of the alkylene structural unit and the content ratio of the conjugated diene monomer unit, it is preferable that the content ratio satisfies the above range.
[0044] (nitrile group-containing monomer unit, conjugated diene monomer unit, alkylene structural unit) The total ratio of the nitrile group-containing monomer units and the conjugated diene monomer units and / or alkylene structural units in the hydrogenated nitrile rubber of the present invention is not particularly limited, but when it is usually 80 mass% or more, preferably 90 mass% or more, more preferably 95 mass% or more, even more preferably 97 mass% or more, and most preferably 99 mass% or more, the dispersion stability of the conductive material dispersion and the cycle characteristics of the electrochemical element can be improved.
[0045] (Other repeating units) The other repeating units are not particularly limited, but may include aromatic vinyl monomer units, acidic group-containing monomer units, and (meth)acrylic acid ester monomer units. The hydrogenated nitrile rubber may contain one type of other repeating unit, or may contain two or more types of other repeating units. In the present invention, "(meth)acrylic" means acrylic and / or methacrylic.
[0046] Examples of aromatic vinyl monomers that can form aromatic vinyl monomer units include styrene, α-methylstyrene, pt-butylstyrene, butoxystyrene, vinyltoluene, chlorostyrene, and vinylnaphthalene. The aromatic vinyl monomers may be used alone or in any combination of two or more at any ratio. Among these, styrene is preferred.
[0047] Examples of the acidic group-containing monomer capable of forming the acidic group-containing monomer unit include a carboxylic acid group-containing monomer, a sulfonic acid group-containing monomer, and a phosphoric acid group-containing monomer. The acidic group-containing monomer may be used alone or in any combination of two or more kinds at any ratio.
[0048] Examples of the carboxylic acid group-containing monomer include monocarboxylic acids and their derivatives, dicarboxylic acids and their acid anhydrides, and their derivatives.
[0049] Examples of the monocarboxylic acid include acrylic acid, methacrylic acid, and crotonic acid. Examples of the monocarboxylic acid derivatives include 2-ethylacrylic acid, isocrotonic acid, α-acetoxyacrylic acid, β-trans-aryloxyacrylic acid, and α-chloro-β-E-methoxyacrylic acid.
[0050] The dicarboxylic acids include maleic acid, fumaric acid, and itaconic acid. Examples of dicarboxylic acid derivatives include methylmaleic acid, dimethylmaleic acid, phenylmaleic acid, chloromaleic acid, dichloromaleic acid, fluoromaleic acid, and maleic acid monoesters such as nonyl maleate, decyl maleate, dodecyl maleate, octadecyl maleate, and fluoroalkyl maleate.
[0051] Examples of the acid anhydrides of dicarboxylic acids include maleic anhydride, acrylic anhydride, methylmaleic anhydride, and dimethylmaleic anhydride.
[0052] Furthermore, as the carboxylic acid group-containing monomer, an acid anhydride that generates a carboxylic acid group by hydrolysis can also be used. Among them, acrylic acid and methacrylic acid are preferred as the carboxylic acid group-containing monomer.
[0053] Examples of the sulfonic acid group-containing monomer include vinyl sulfonic acid, methyl vinyl sulfonic acid, (meth)allyl sulfonic acid, styrene sulfonic acid, (meth)acrylic acid-2-ethyl sulfonate, 2-acrylamido-2-methylpropanesulfonic acid, and 3-allyloxy-2-hydroxypropanesulfonic acid. In the present invention, "(meth)allyl" means allyl and / or methallyl.
[0054] Examples of the phosphate group-containing monomer include 2-(meth)acryloyloxyethyl phosphate, methyl-2-(meth)acryloyloxyethyl phosphate, and ethyl-(meth)acryloyloxyethyl phosphate. In the present invention, "(meth)acryloyl" means acryloyl and / or methacryloyl.
[0055] Examples of (meth)acrylic acid ester monomers capable of forming a (meth)acrylic acid ester monomer unit include methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, t-butyl acrylate, pentyl acrylate, hexyl acrylate, heptyl acrylate, octyl acrylate, 2-ethylhexyl acrylate, nonyl acrylate, decyl acrylate, lauryl acrylate, n-tetradecyl acrylate, and stearyl acrylate. Acrylic acid alkyl esters include methacrylic acid alkyl esters such as methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, t-butyl methacrylate, pentyl methacrylate, hexyl methacrylate, heptyl methacrylate, octyl methacrylate, 2-ethylhexyl methacrylate, nonyl methacrylate, decyl methacrylate, lauryl methacrylate, n-tetradecyl methacrylate, and stearyl methacrylate. The (meth)acrylic acid ester monomers may be used alone or in combination of two or more kinds at any ratio.
[0056] The content ratio of other repeating units in the hydrogenated nitrile rubber is preferably 0% by mass or more and 30% by mass or less, more preferably 0% by mass or more and 20% by mass or less, even more preferably 0% by mass or more and 10% by mass or less, particularly preferably 0% by mass or more and 5% by mass or less, and most preferably 0% by mass or more and 3% by mass or less, based on 100% by mass of all repeating units in the nitrile polymer.
[0057] <Hydrogenated nitrile rubber> The hydrogenated nitrile rubber of the present invention has the above repeating unit and is characterized by having a specific weight average molecular weight (Mw), an iodine value, and a calcium (Ca) content within specific ranges.
[0058] The weight average molecular weight (Mw) of the hydrogenated nitrile rubber of the present invention is in the range of 1,000 to 1,000,000, preferably 2,000 to 500,000, more preferably 4,000 to 300,000, and most preferably 5,000 to 250,000. If the weight average molecular weight (Mw) of the hydrogenated nitrile rubber is in this range, the dispersion stability of the conductive material dispersion can be increased, and the peel strength of the obtained electrode can be increased, which is preferable.
[0059] The iodine value of the hydrogenated nitrile rubber of the present invention is 60 to 120 mg / 100 mg, preferably 60 to 100 mg / 100 mg, more preferably 60 to 90 mg / 100 mg, further preferably 60 to 80 mg / 100 mg, and most preferably 65 to 80 mg / 100 mg. When the iodine value of the hydrogenated nitrile rubber is in this range, the viscosity characteristics of the conductive material dispersion, the peel strength of the electrode, and the output characteristics of the electrochemical element are highly balanced, which is preferable.
[0060] The calcium (Ca) content in the hydrogenated nitrile rubber of the present invention is in the range of 50 to 2500 ppm, preferably 60 to 2500 ppm, more preferably 80 to 1500 ppm, further preferably 100 to 800 ppm, and most preferably 200 to 600 ppm. When the Ca content in the hydrogenated nitrile rubber is in this range, the peel strength of the electrode can be significantly increased without impairing the stability of the conductive material dispersion liquid, which is preferable. In addition, when the Ca content in the hydrogenated nitrile rubber is in this range, the cycle characteristics of the obtained electrochemical element and the effect of suppressing cracking of the electrode active material after cycle testing can be improved, which is preferable. The Ca content in the hydrogenated nitrile rubber in the case of highly improving the peel strength of the electrode and the cycle characteristics of the lithium ion secondary battery is not particularly limited, but is usually 50 ppm or more, preferably 100 ppm or more, more preferably 150 ppm or more, even more preferably 200 ppm or more, particularly preferably 250 ppm or more, and most preferably 300 ppm or more, and the upper limit is not particularly limited, but is usually 2500 ppm or less, preferably 2000 ppm or less, more preferably 1800 ppm or less, even more preferably 1600 ppm or less, and most preferably 1500 ppm or less.
[0061] The magnesium (Mg) content in the hydrogenated nitrile rubber of the present invention is not particularly limited, but is usually 50 ppm or less, preferably 30 ppm or less, and more preferably 10 ppm or less. When the Mg content in the hydrogenated nitrile rubber is in this range, cracking of the active material in the electrode is suppressed, and the cycle characteristics of the electrochemical element are improved, which is preferable.
[0062] The sodium (Na) content in the hydrogenated nitrile rubber of the present invention is not particularly limited, but is usually 300 ppm or less, preferably 250 ppm or less, more preferably 200 ppm or less, even more preferably 150 ppm or less, particularly preferably 100 ppm or less, and most preferably 50 ppm or less. When the Na content in the hydrogenated nitrile rubber is in this range, cracking of the active material in the electrode is suppressed, and the cycle characteristics of the electrochemical element are improved, which is preferable.
[0063] The rhodium (Rh) and / or ruthenium (Ru) content (total amount of Rh and Ru) in the hydrogenated nitrile rubber of the present invention is not particularly limited, but when it is usually 50 ppm or less, preferably 30 ppm or less, more preferably 20 ppm or less, cracking of the active material in the produced electrode can be suppressed, which is suitable.
[0064] The palladium (Pd) content in the hydrogenated nitrile rubber of the present invention is not particularly limited, but is usually 100 ppm or less, preferably 50 ppm or less, more preferably 30 ppm or less, further preferably 10 ppm or less, and most preferably 5 ppm or less. When the Pd content in the hydrogenated nitrile rubber is in this range, cracking of the active material in the electrode is suppressed, and the cycle characteristics of the electrochemical element are improved, which is preferable.
[0065] The bulk density of the hydrogenated nitrile rubber of the present invention is not particularly limited, but is usually 0.6 g / cm. 3 More than 0.7 g / cm, preferably 0.7 g / cm 3 More preferably, 0.8 g / cm 3 More preferably, 0.85 g / cm 3 More than 0.9 g / cm 3 The upper limit of the bulk density of the hydrogenated nitrile rubber is not particularly limited, but is usually 1.2 g / cm. 3 Less than or equal to 1.15 g / cm 3 Less than or equal to 1.1 g / cm 3 More preferably, 1.05 g / cm 3 Below 1 g / cm, most preferably 3 When the bulk density of the hydrogenated nitrile rubber is within this range, the effect of the phenol-based antioxidant is highly enhanced, the stability of the conductive material dispersion is excellent, and it is preferable in terms of preventing the cycle characteristics of the electrochemical element and cracking of the active material after cycle testing.
[0066] The bulk density of the hydrogenated nitrile rubber can be easily adjusted, for example, by drying with a screw extruder described below or by baling the hydrogenated nitrile rubber.
[0067] The water content of the hydrogenated nitrile rubber of the present invention is not particularly limited, but is usually less than 1% by mass, preferably 0.8% by mass or less, and more preferably 0.6% by mass or less, and is therefore suitable for excellent storage stability.
[0068] The Mooney viscosity (ML1+4, 100°C) of the hydrogenated nitrile rubber of the present invention is not particularly limited, but when it is in the range of usually 10 to 150, preferably 15 to 100, more preferably 20 to 80, the conductive material dispersibility and the peel strength at the electrode are highly balanced, which is suitable.
[0069] The hydrogenated nitrile rubber of the present invention may contain a phenol-based antioxidant as necessary. When the hydrogenated nitrile rubber of the present invention contains a phenol-based antioxidant, the stability of the conductive material dispersion is significantly improved, the smoothness of the produced electrode is improved, and the variation in electrode properties is reduced, which is preferable.
[0070] The phenol-based antiaging agent is not particularly limited, and examples thereof include 2,6-di-t-butylphenol, 2,6-di-t-butyl-4-methylphenol, 2,6-di-t-butyl-α-dimethylamino-p-cresol, 3-(4-hydroxy-3,5-di-t-butylphenyl)butyl propionate, 3-(4-hydroxy-3,5-di-t-butylphenyl)hexyl propionate, and 3-(4-hydroxy-3,5-di-t-butylphenyl)octyl propionate. ethyl, 3-(4-hydroxy-3,5-di-t-butylphenyl)propionate, decyl 3-(4-hydroxy-3,5-di-t-butylphenyl)propionate, dodecyl 3-(4-hydroxy-3,5-di-t-butylphenyl)propionate, 2,2-methylenebis(4-methyl-6-tert-butylphenol), and the like, and preferred are 2,6-di-t-butyl-4-methylphenol (dibutylhydroxytoluene = BHT) and 2,2-methylenebis(4-methyl-6-tert-butylphenol) (MBBP).
[0071] The content of the phenol-based antioxidant in the hydrogenated nitrile rubber is not particularly limited, but is usually in the range of 0.001 to 2 mass %, preferably 0.01 to 1 mass %, and more preferably 0.1 to 0.5 mass %.
[0072] The hydrogenated nitrile rubber of the present invention is not particularly limited, but is preferably obtained by emulsion polymerization of a nitrile group-containing monomer and a conjugated diene monomer, and hydrogenating the polymer coagulated with calcium chloride. When the emulsion polymerization liquid is coagulated to obtain a polymer, the size, shape, or properties of the water-containing crumbs produced will be completely different depending on the type of coagulant used, and the residues of various secondary materials in the polymerization and coagulation steps that can be removed in the subsequent washing and dehydration steps will be different. It is not possible to prove all of the trace residues of these secondary materials and their reactants, and especially when used in the electrochemical element of the present invention, these slight residues affect various characteristics. Therefore, for electrochemical element applications, it is preferable to use a polymer obtained by hydrogenating calcium chloride as a coagulant. Among calcium compounds, those using calcium chloride are preferable because they are easily removed in the subsequent washing and purification steps, and can reduce the residues in the hydrogenated nitrile rubber.
[0073] The hydrogenated nitrile rubber of the present invention is preferably obtained by emulsion polymerizing a nitrile group-containing monomer and a conjugated diene monomer, adding the phenol-based antioxidant, and then hydrogenating the polymer solidified with calcium chloride.
[0074] The effect of the specific antioxidant is much higher and more preferable when it is added to the emulsion polymerization liquid obtained by emulsion polymerization of a nitrile group-containing monomer and a conjugated diene monomer, rather than being mixed with the hydrogenated nitrile rubber after production. Although it is not possible to measure this, it is believed that the phenol-based antioxidant is finely and uniformly dispersed in the hydrogenated nitrile rubber obtained as it is by coagulating the emulsion polymerization liquid in which the phenol-based antioxidant is uniformly dispersed with calcium chloride, thereby exhibiting a high effect.
[0075] <Method of producing hydrogenated nitrile rubber> The method for producing hydrogenated nitrile rubber of the present invention is not particularly limited, but is characterized in that, for example, a polymer (nitrile rubber) obtained by emulsion polymerization of a monomer component containing a nitrile group-containing monomer and a conjugated diene monomer and coagulating the polymer with calcium chloride is hydrogenated with a rhodium-based catalyst and / or a ruthenium-based catalyst.
[0076] (Emulsion Polymerization) The monomer components used are the same as those described for the monomer units, and the amount used may be appropriately selected so as to obtain the monomer composition of the hydrogenated nitrile rubber.
[0077] The emulsifier is not particularly limited, but examples thereof include anionic emulsifiers, cationic emulsifiers, and nonionic emulsifiers, and is preferably anionic emulsifiers.
[0078] The anionic emulsifier is not particularly limited, and examples thereof include salts of fatty acids such as myristic acid, palmitic acid, oleic acid, and linolenic acid; alkylbenzenesulfonates such as sodium dodecylbenzenesulfonate; sulfates such as sodium lauryl sulfate, and phosphates such as polyoxyalkylene alkyl ether phosphates; and alkylsulfosuccinates. Among these anionic emulsifiers, fatty acid salts and sulfates are preferred, and fatty acid salts are particularly preferred. Suitable sulfates include, for example, sodium lauryl sulfate, ammonium lauryl sulfate, sodium myristyl sulfate, sodium laureth sulfate, sodium polyoxyethylene alkyl sulfate, and sodium polyoxyethylene alkylaryl sulfate. Suitable fatty acid salts include, for example, potassium oleate, sodium oleate, and potassium palmitate, and potassium oleate is particularly preferred.
[0079] These emulsifiers can be used alone or in combination of two or more. The amount used is usually 0.01 to 10 parts by mass, preferably 0.1 to 5 parts by mass, and more preferably 1 to 3 parts by mass, per 100 parts by mass of the monomer component.
[0080] The emulsion polymerization method may be a conventional method, and may be any of batch, semi-batch, and continuous. The polymerization temperature and polymerization time are not particularly limited and may be appropriately selected depending on the type of polymerization initiator used. The polymerization temperature is usually in the range of 0 to 100°C, preferably 5 to 80°C, and more preferably 10 to 50°C, and the polymerization time is usually 0.5 to 100 hours, and preferably 1 to 10 hours.
[0081] A phenolic antioxidant can be added to the emulsion polymerization liquid after emulsion polymerization as necessary. The phenolic antioxidant used is the same as the phenolic antioxidant exemplified in the hydrogenated nitrile rubber, and the method of adding the phenolic antioxidant to the emulsion polymerization liquid is not particularly limited and may be in accordance with a conventional method, for example, it may be added as it is or may be emulsified with an emulsifier and then added. The amount of the phenolic antioxidant used may be appropriately selected so as to be the content of the antioxidant in the hydrogenated nitrile rubber of the present invention, and is usually in the range of 0.001 to 15 parts by mass, preferably 0.01 to 10 parts by mass, more preferably 0.1 to 5 parts by mass, particularly preferably 0.3 to 3 parts by mass, and most preferably 0.5 to 2 parts by mass, relative to 100 parts by mass of the monomer component.
[0082] (solidification process) The present invention is characterized in that the emulsion polymerization liquid obtained above is coagulated with calcium chloride. In particular, coagulation with calcium chloride is preferable because the coagulation activity of the emulsion polymerization liquid is high and only a small amount of calcium chloride is added, and it is easy to remove from the polymer by washing with water or activated carbon treatment in a subsequent process. Therefore, it is preferable because it is easy to control the Ca content in the hydrogenated nitrile rubber produced. In addition, when an electrochemical element is produced using a hydrogenated nitrile rubber having a Ca content within a specific range, it is preferable because it is possible to increase the dispersibility of the conductive material dispersion liquid, while increasing the peel strength of the electrode and suppressing cracking of the electrode active material after cycle characteristics.
[0083] The calcium chloride used is usually used as an aqueous solution, and the coagulant concentration of the aqueous solution is usually in the range of 0.1 to 70 mass%, preferably 1 to 60 mass%, more preferably 5 to 50 mass%, and particularly preferably 10 to 30 mass%, which is suitable for concentrating the particle size of the generated hydrous crumbs uniformly in a specific region.
[0084] The temperature in the solidification reaction is not particularly limited, but a temperature in the range of usually 40°C or higher, preferably 40 to 90°C, and more preferably 50 to 80°C, is suitable for producing uniform water-containing crumbs.
[0085] After the coagulation reaction, the coagulated product is washed with water and then dried to obtain a polymer to be hydrogenated.
[0086] (Hydrogenation process) The present invention is characterized in that the polymer obtained above is subjected to a hydrogenation reaction using a rhodium-based catalyst and / or a ruthenium-based catalyst.
[0087] The hydrogenation reaction using a rhodium-based catalyst and / or a ruthenium-based catalyst may be carried out according to a conventional method, for example, the method described in Japanese Patent No. 4509792. Preferably, the hydrogenation reaction uses a ruthenium-based Grubbs catalyst and / or a rhodium-based Wilkinson catalyst.
[0088] Hydrogenation reactions using Grubbs catalyst The Grubbs catalyst to be used is not particularly limited, but suitable examples include bis(tricyclohexylphosphine)benzylidene ruthenium dichloride, 1,3-bis(2,4,6-trimethylphenyl)-2-(imidazolidinylidene)(dichlorophenylmethylene)(tricyclohexylphosphine)ruthenium, and the like.
[0089] Grubbs catalyst has the property of metathesis of hydrogenated nitrile rubber using coolefin, and is used to adjust the molecular weight of hydrogenated nitrile rubber. In addition, in the presence of hydrogen, Grubbs catalyst is converted to the dihydride complex (PR3)2RuCl2H2, which is an olefin hydrogenation catalyst. Therefore, in the reaction using Grubbs catalyst, the metathesis reaction is first carried out using coolefin, and then hydrogen is introduced to carry out the hydrogenation reaction.
[0090] Examples of the coolefin to be used include olefins having 2 to 16 carbon atoms, such as ethylene, isobutane, styrene, and 1-hexane; and functional group-containing unsaturated compounds, such as cis-2-butene-1,4-diol, 3-butene-1-amine, vinyltrimethoxysilane, methoxypolyalkylene glycol methacrylate, and 2-(methacryloyloxy)ethanesulfonic acid. Of these, functional group-containing unsaturated compounds are preferred.
[0091] The amount of the coolefin used is usually in the range of 0.1 to 20 parts by mass, preferably 0.5 to 10 parts by mass, and more preferably 1 to 5 parts by mass, based on 100 parts by mass of the polymer.
[0092] The reaction can be carried out in any solvent that does not inactivate the catalyst or interfere with the reaction. Preferred solvents include, but are not limited to, dichloromethane, benzene, toluene, tetrahydrofuran, cyclohexane, monochlorobenzene (MCB), and the like, most preferably MCB. In some cases, the coolefin itself can act as the solvent, in which case no other solvent is required.
[0093] The polymer concentration in the metathesis reaction is not critical, but is usually in the range of 1 to 20% by mass, preferably 6 to 15% by mass.
[0094] The reaction solution in the metathesis reaction is usually stirred vigorously, for example, at a speed in the range of 200 to 1000 rpm, preferably 300 to 900 rpm, and more preferably 500 to 800 rpm.
[0095] The temperature of the metathesis reaction is usually in the range of 20 to 140° C., preferably 60 to 120° C. The reaction time depends on many factors such as the cement concentration, the amount of catalyst used, and the reaction temperature, but is usually completed within 2 hours. The progress of the metathesis reaction can be monitored using standard analytical methods, such as GPC or solution viscosity.
[0096] The hydrogenation reaction can be carried out by filling the reaction vessel with hydrogen after the above metathesis. The pressure of the hydrogenation reaction is not particularly limited, but is usually in the range of 0.1 to 30 MPa, preferably 1 to 20 MPa.
[0097] In addition, it is possible to carry out only the hydrogenation reaction by filling the reactor with hydrogen from the beginning without using a co-olefin.
[0098] Wilkinson's Catalyst for Hydrogenation The hydrogenation reaction using Wilkinson's catalyst ((PPh3)3RhCl) is advantageous because it can be carried out in the reaction vessel after the metathesis reaction using Grubbs' catalyst, by adding the hydrogenation catalyst to the vessel without isolating the metathesis product.
[0099] Examples of the solvent for the hydrogenation reaction include acetone, methyl ethyl ketone, ethyl acetate, tetrahydrofuran, 1,3-dioxane, benzene, toluene, methylene chloride, chloroform, monochlorobenzene (MCB), dichlorobenzene, etc. Among these, MCB is particularly suitable as a good solvent for both the nitrile group-containing nitrile rubber before hydrogenation and the hydrogenated nitrile rubber after hydrogenation.
[0100] The amount of the hydrogenation catalyst used may be appropriately selected depending on the purpose of use and the iodine value, but is usually in the range of 0.001 to 0.5 parts by mass, preferably 0.005 to 0.1 parts by mass, or 0.01 to 0.05 parts by mass based on 100 parts by mass of the polymer before hydrogenation.
[0101] In the hydrogenation reaction, a cocatalyst can be used as necessary. Examples of the cocatalyst include phosphine, diphosphine, triphenylphosphine, etc., and preferably triphenylphosphine. The amount of the cocatalyst used is usually in the range of 0.01 to 15 parts by mass, preferably 0.1 to 10 parts by mass, and more preferably 0.5 to 5 parts by mass, based on 100 parts by mass of the polymer to be hydrogenated.
[0102] The pressure for the hydrogenation reaction is not particularly limited, but is usually in the range of 0.1 to 30 MPa, preferably 1 to 20 MPa, and more preferably 5 to 15 MPa.
[0103] The hydrogenation reaction temperature is usually in the range of 30 to 200° C., preferably 50 to 170° C., and more preferably 100 to 150° C. The reaction time is usually 1 to 50 hours, and preferably 2 to 25 hours.
[0104] The hydrogenation reaction can be stopped once the desired hydrogenation level has been reached by depressurizing the reactor or by cooling it. Residual hydrogen is usually removed by a nitrogen purge. The hydrogenation catalyst can also be removed prior to removal of the solvent and isolation of the hydrogenated nitrile rubber from the organic layer.
[0105] After the hydrogenation reaction, the solvent is removed and the product is dried to obtain hydrogenated nitrile rubber.
[0106] <Drying of hydrogenated nitrile rubber using a screw-type extruder> In drying the hydrogenated nitrile rubber, drying with a screw-type extruder is preferable because it can remove the air present therein and increase the bulk density. Specifically, the hydrogenated nitrile rubber-containing solution after the hydrogenation reaction or after the purification step after the hydrogenation reaction is solidified, and the resulting water-containing crumbs can be dried using a screw-type extruder.
[0107] (solidification process) The coagulation step of the filtrate containing hydrogenated nitrile rubber from which impurities have been removed and obtained in the above purification step is not particularly limited, and may be performed according to a conventional method. Specific coagulation methods include a method of contacting with a coagulant and a method of contacting with a large amount of poor solvent, and preferably a method of contacting with a large amount of poor solvent. The poor solvent is not particularly limited, but methanol, water, steam, etc. are preferably used. The coagulation reaction may be appropriately selected, and for example, the coagulation reaction temperature is usually selected within the range of room temperature to 100°C, and the coagulation reaction time is appropriately selected within the range of several minutes to several hours.
[0108] The hydrous crumb of the hydrogenated nitrile rubber produced by the coagulation reaction can be washed as necessary. The washing method is not particularly limited and may be a conventional method, but washing with a large amount of water is efficient. The amount of water used is usually 10 to 500 times, preferably 25 to 250 times, and more preferably 50 to 100 times, relative to 100 parts by mass of the polymer. The temperature of the water used for washing is not particularly limited, but it is preferable to use warm water, and it is usually 40°C or higher, preferably 40 to 100°C, more preferably 50 to 90°C, and most preferably 60 to 80°C, which is preferable because it can significantly increase the washing efficiency. By setting the temperature of the washing water to the above lower limit or higher, the emulsifier and coagulant are released from the hydrous crumb, and the washing efficiency is further improved.
[0109] After coagulation, or alternatively after washing, the wet crumbs can be isolated by filtration.
[0110] (drying process) In the present invention, the hydrous crumb of the hydrogenated nitrile rubber isolated above is dried using a screw extruder. The hydrogenated nitrile rubber is melt-kneaded and dried under reduced pressure in the screw extruder, whereby the air present inside is removed to obtain a dry rubber (hydrogenated nitrile rubber) having a high bulk density. When used as a positive electrode material, the stability of the conductive material dispersion is excellent, and the peel strength of the electrochemical element electrode and cracking of the active material layer after cycle testing are prevented, making this suitable.
[0111] -Screw type extruder- Dehydration of the dehydration barrel The dehydration of the hydrous crumb is carried out in a dehydration barrel having a dehydration slit. The opening of the dehydration slit may be appropriately selected depending on the conditions of use, but when it is in the range of usually 0.1 to 1 mm, preferably 0.2 to 0.6 mm, the loss of the hydrous crumb is small and the hydrous crumb can be efficiently dehydrated.
[0112] The number of dehydration barrels in the screw extruder is not particularly limited, but it is usually suitable to have multiple barrels, preferably 2 to 10 barrels, and more preferably 3 to 6 barrels, in order to efficiently dehydrate the viscous hydrogenated nitrile rubber.
[0113] The set temperature of the dehydration barrel is appropriately selected depending on the type of hydrogenated nitrile rubber, the ash content, the water content, the operating conditions, etc., but is usually in the range of 60 to 150° C., preferably 70 to 140° C., and more preferably 80 to 130° C. The set temperature of the dehydration barrel for dehydrating in a drainage state is usually in the range of 60 to 120° C., preferably 70 to 110° C., and more preferably 80 to 100° C. The set temperature of the dehydration barrel for drying in an exhaust steam state is usually in the range of 100 to 150° C., preferably 105 to 140° C., and more preferably 110 to 130° C.
[0114] The moisture content after dehydration, in which moisture is squeezed out from the hydrous crumb, is not particularly limited, but is usually 1 to 45 mass%, preferably 1 to 40 mass%, more preferably 5 to 35 mass%, and particularly preferably 10 to 35 mass%.
[0115] Drying of the drying barrel The water-containing crumbs dehydrated in the dehydrating barrel are further dried in the drying barrel under reduced pressure. The degree of reduced pressure in the drying barrel may be appropriately selected, but is usually 1 to 50 kPa, preferably 2 to 30 kPa, and more preferably 3 to 20 kPa, which is suitable for efficiently drying the water-containing crumbs. In addition, by extruding the molten hydrogenated nitrile rubber inside the drying barrel under reduced pressure, the air present therein is also removed, and a sheet-like hydrogenated nitrile rubber having a high bulk density can be produced, which is suitable.
[0116] The set temperature of the drying barrel may be appropriately selected, but when it is usually in the range of 100 to 250°C, preferably 110 to 200°C, and more preferably 120 to 180°C, the hydrogenated nitrile rubber can be dried efficiently without discoloration or deterioration.
[0117] The number of drying barrels in the screw extruder is not particularly limited, but is usually more than one, preferably 2 to 10, more preferably 3 to 8. When there are more than one drying barrels, the degree of reduced pressure may be similar for all drying barrels or may be different. When there are more than one drying barrels, the set temperatures may be similar for all drying barrels or may be different, but it is preferable to set the temperature of the discharge part (closer to the die) higher than the temperature of the introduction part (closer to the dehydration barrel) in order to increase the drying efficiency.
[0118] The water content of the dried rubber after drying is usually less than 1% by mass, preferably 0.8% by mass or less, and more preferably 0.6% by mass or less.
[0119] Hydrogenated nitrile rubber extrusion (die section) The hydrogenated nitrile rubber dehydrated and dried in the screw section of the dehydrating barrel and the drying barrel is sent to a screw-free straightening die section. A breaker plate or a wire mesh may or may not be provided between the screw section and the die section.
[0120] The extruded hydrogenated nitrile rubber can be obtained in various shapes such as granules, columns, round rods, sheets, etc., depending on the shape of the die nozzle. However, it is preferable to extrude the rubber in sheet form using a substantially rectangular die shape, since this produces a dried rubber with less air entrapment, a large bulk density, and excellent storage stability.
[0121] The resin pressure in the die section is not particularly limited, but when it is in the range of usually 0.1 to 10 MPa, preferably 0.5 to 5 MPa, and more preferably 1 to 3 MPa, it is suitable since it reduces air entrainment and provides excellent productivity.
[0122] Screw type extruder and operating conditions The screw length (L) of the screw type extruder used may be appropriately selected depending on the purpose of use, but is usually in the range of 2000 to 15000 mm, preferably 2500 to 10000 mm, and more preferably 3000 to 7000 mm.
[0123] The screw diameter (D) of the screw type extruder used may be appropriately selected depending on the purpose of use, but is usually in the range of 50 to 250 mm, preferably 70 to 200 mm, and more preferably 80 to 160 mm.
[0124] The ratio (L / D) of the screw length (L) to the screw diameter (D) of the screw extruder used is not particularly limited, but is usually in the range of 10 to 150, preferably 15 to 100, more preferably 20 to 80, and particularly preferably 30 to 60, which is suitable for reducing the moisture content to less than 1 mass% without causing a decrease in the molecular weight of the dried rubber or scorching.
[0125] The rotation speed (N) of the screw extruder used may be appropriately selected depending on various conditions, but is usually 10 to 1000 rpm, preferably 30 to 800 rpm, more preferably 50 to 600 rpm, and most preferably 100 to 400 rpm.
[0126] The extrusion rate (Q) of the screw extruder used is not particularly limited, but is usually in the range of 100 to 1500 kg / hr, preferably 120 to 1200 kg / hr, more preferably 150 to 1000 kg / hr, and most preferably 200 to 800 kg / hr.
[0127] The ratio (Q / N) of the extrusion rate (Q) to the rotation speed (N) of the screw extruder used is not particularly limited, but is usually in the range of 1 to 10, preferably 1 to 5, and more preferably 1 to 3.
[0128] Dry rubber The shape of the dried rubber extruded from the screw-type extruder is not particularly limited, and examples thereof include crumb, powder, rod, and sheet shapes, with the sheet shape being particularly preferred.
[0129] <Hydrogenated nitrile rubber veil> The hydrogenated nitrile rubber bale of the present invention can be produced by baling the above-mentioned dried hydrogenated nitrile rubber.
[0130] The hydrogenated nitrile rubber bale of the present invention is made of the above-mentioned hydrogenated nitrile rubber, and by baling it, the effect of the hydrogenated nitrile rubber of the present invention can be preferably maintained even during storage.
[0131] The shape of the hydrogenated nitrile rubber veil of the present invention is not particularly limited, but is usually a rectangular parallelepiped. The size is not particularly limited, but the width is usually in the range of 100 to 800 mm, preferably 200 to 500 mm, more preferably 250 to 450 mm, the length is usually in the range of 300 to 1200 mm, preferably 400 to 1000 mm, more preferably 500 to 800 mm, and the height is usually in the range of 50 to 500 mm, preferably 100 to 300 mm, more preferably 150 to 250 mm.
[0132] The weight average molecular weight (Mw), iodine value, Rh content, Ru content, Pd content, Ca content, Na content and Mg content of the hydrogenated nitrile rubber veil of the present invention are the same as those of the hydrogenated nitrile rubber.
[0133] The water content of the hydrogenated nitrile rubber bale of the present invention is not particularly limited, but is usually less than 1% by mass, preferably 0.8% by mass or less, and more preferably 0.6% by mass or less, and is therefore suitable for excellent storage stability.
[0134] The Mooney viscosity (ML1+4, 100°C) of the hydrogenated nitrile rubber veil of the present invention is not particularly limited, but when it is in the range of usually 10 to 150, preferably 15 to 100, more preferably 20 to 80, the conductive material dispersibility and the peel strength at the electrode are highly balanced, which is suitable.
[0135] The bulk density of the hydrogenated nitrile rubber veil of the present invention is not particularly limited, but is usually 0.6 g / cm 3 More than 0.7 g / cm, preferably 0.7 g / cm 3 More preferably, 0.8 g / cm 3 More preferably, 0.85 g / cm 3 More than 0.9 g / cm 3 The upper limit of the bulk density of the hydrogenated nitrile rubber veil is not particularly limited, but is usually 1.2 g / cm 3 Less than or equal to 1.15 g / cm 3 Less than or equal to 1.1 g / cm 3 More preferably, 1.05 g / cm 3 Below 1 g / cm, most preferably 3 When the bulk density of the hydrogenated nitrile rubber veil is within this range, the effect of the phenol-based antioxidant is highly enhanced, the stability of the conductive material dispersion liquid is excellent, and the cycle characteristics of the electrochemical device and cracking of the active material after cycle testing can be prevented.
[0136] Baling of hydrogenated nitrile rubber may be performed according to a conventional method, for example, by putting the above-mentioned dried rubber into a baler and compressing it. The compression pressure is appropriately selected depending on the purpose of use, but is usually in the range of 0.1 to 15 MPa, preferably 0.5 to 10 MPa, and more preferably 1 to 5 MPa. The compression time is not particularly limited, but is usually in the range of 1 to 60 seconds, preferably 5 to 50 seconds, and more preferably 10 to 40 seconds. Alternatively, a sheet-like dried rubber may be produced and layered to form a bale. Baling by layering sheets is easy to produce, and furthermore, a bale with few bubbles (high bulk density) can be produced, which is preferable because of its excellent storage stability.
[0137] In the present invention, further, by laminating the sheet-like dried rubber (hydrogenated nitrile rubber) extruded from the screw-type extruder, a suitable hydrogenated nitrile rubber bale having a large bulk density can be easily produced.
[0138] <Positive electrode binder> The positive electrode binder of the present invention is obtained by dissolving or dispersing the hydrogenated nitrile rubber or the hydrogenated nitrile rubber veil in N-methylpyrrolidone (NMP), and is suitable as a material for producing a positive electrode of an electrochemical element.
[0139] The binder for the positive electrode of the present invention can be combined with other components as necessary in addition to the hydrogenated nitrile rubber and NMP. The other components are not particularly limited, but examples thereof include binders other than the hydrogenated nitrile rubber (polyvinylidene fluoride, polyacrylate, etc.), reinforcing materials, leveling agents, viscosity modifiers, and electrolyte additives. These are not particularly limited as long as they do not affect the battery reaction, and known ones can be used. The binder for the positive electrode of the present invention may also contain a solvent other than NMP to the extent that the characteristics of the present invention are not impaired. Note that these other components may be used alone, or two or more may be used in combination at any ratio.
[0140] The solid content of the binder for a positive electrode of the present invention is not particularly limited, but is usually in the range of 0.1 to 40 mass %, preferably 0.5 to 20 mass %, and more preferably 1 to 10 mass %.
[0141] The hydrogenated nitrile rubber, NMP and other components used as necessary may be mixed in a conventional manner.
[0142] <Electrodes for electrochemical elements> The positive electrode binder of the present invention can be used in the manufacture of a positive electrode by mixing it with a conductive material and then mixing it with a positive electrode active material to obtain a positive electrode mixture layer slurry, which can be applied onto a current collector and dried.
[0143] (Conductive material) The conductive material is a component that functions to ensure electrical contact between electrode active materials. As the conductive material, a carbonaceous material can be suitably used. Examples of such carbonaceous materials include carbon black (e.g., acetylene black, Ketjen Black (registered trademark), furnace black, etc.), single-walled or multi-walled carbon nanotubes (multi-walled carbon nanotubes include cup-stacked types), carbon nanohorns, vapor-grown carbon fibers, milled carbon fibers obtained by crushing polymer fibers after firing, single-walled or multi-walled graphene, and carbon nonwoven fabric sheets obtained by firing nonwoven fabrics made of polymer fibers. These may be used alone or in combination of two or more types in any ratio. Among these, carbon nanotubes (CNTs) are preferred from the viewpoint of forming a good conductive path.
[0144] When mixing the binder for positive electrode of the present invention and the conductive material, the ratio of the conductive material to the binder for positive electrode is not particularly limited. For example, the conductive material and the binder for positive electrode may be mixed in such a manner that the hydrogenated nitrile rubber is usually mixed in the range of 1 to 100 parts by mass, preferably 5 to 50 parts by mass, more preferably 10 to 30 parts by mass per 100 parts by mass of the conductive material in the obtained conductive material dispersion. In addition, when mixing the binder for positive electrode and the conductive material, NMP can be added as necessary to adjust the viscosity.
[0145] When the solid content concentration of the binder for the positive electrode of the present invention and the conductive material is mixed, it is usually 0.01% by mass or more, preferably 1.0% by mass or more, more preferably 3.0% by mass or more, and the upper limit is usually 10.0% by mass or less, preferably 9.0% by mass or less, more preferably 8.0% by mass or less. If the solid content concentration is at least the above lower limit value, the coatability of the conductive material dispersion can be improved. Further, if the solid content concentration is at most the above upper limit value, the rate characteristics of the obtained electrochemical device can be improved.
[0146] The method for mixing the binder for the positive electrode of the present invention and the conductive material is not particularly limited, and for example, it can be mixed using a known mixing device.
[0147] (Positive electrode active material) The positive electrode active material is not particularly limited, but when the electrochemical device is a lithium ion secondary battery, metal oxides containing lithium (Li) can be mentioned. And as the positive electrode active material, in addition to lithium (Li), a positive electrode active material containing at least one selected from the group consisting of cobalt (Co), nickel (Ni), manganese (Mn), and iron (Fe) is preferable. Such positive electrode active materials include lithium-containing cobalt oxide (LiCoO2), lithium manganate (LiMn2O4), lithium-containing nickel oxide (LiNiO2), lithium-containing composite oxides of Co-Ni-Mn, lithium-containing composite oxides of Ni-Mn-Al, lithium-containing composite oxides of Ni-Co-Al, olivine-type lithium manganese phosphate (LiMnPO4), olivine-type lithium iron phosphate (LiFePO4), Li 1+x Mn 2-x O4 (0 < X < 2) lithium-excess spinel compounds represented by, Li[Ni 0.17 Li 0.2 Co 0.07 Mn 0.56 O2, LiNi 0.5 Mn 1.5 O4, Li[Ni 0.5 Co 0.2 Mn 0.3]O2. The particle size of the positive electrode active material is not particularly limited and can be the same as that of a conventionally used electrode active material. The positive electrode active material may be used alone or in combination of two or more kinds in any ratio.
[0148] The positive electrode active material can be mixed with the mixture of the positive electrode binder and the conductive material to form a positive electrode composite layer slurry. The mixing method is not particularly limited, and can be performed using a known mixing device. The amount of the positive electrode active material is not particularly limited, and can be within the range of conventional use.
[0149] <Electrodes for electrochemical elements> In the present invention, the positive electrode can be obtained by applying the positive electrode mixture layer slurry onto a current collector and drying it. Since the positive electrode mixture layer is formed from the positive electrode binder containing the hydrogenated nitrile rubber of the present invention, the peel strength of the positive electrode can be significantly increased. EXAMPLES
[0150] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the following description, the units "%", "ppm" and "parts" that represent amounts are based on mass unless otherwise specified.
[0151] In a polymer produced by copolymerizing a plurality of types of monomers, the ratio of a monomer unit formed by polymerizing a certain monomer in the polymer usually coincides with the ratio (feed ratio) of the certain monomer in all monomers used in the polymerization of the polymer, unless otherwise specified. In addition, when a polymer is a hydrogenated polymer obtained by hydrogenating a polymer containing a conjugated diene monomer unit, the total content ratio of unhydrogenated conjugated diene monomer units and alkylene structural units as hydrogenated conjugated diene monomer units in the hydrogenated polymer coincides with the ratio (feed ratio) of the conjugated diene monomer in all monomers used in the polymerization of the polymer.
[0152] In the examples and comparative examples, various measurements and evaluations were carried out according to the following methods.
[0153] <Iodine value> The iodine value of the hydrogenated nitrile rubber was measured in accordance with JIS K 6235.
[0154] <Metal content> About 0.5g was collected from the hydrogenated nitrile rubber bale, dissolved in about 5mL of concentrated sulfuric acid, carbonized on a heater, and then incinerated in an electric furnace at 1000°C for about 3 hours. After cooling, about 2mL of concentrated nitric acid was gradually added to perform wet decomposition. After decomposition, the acid was concentrated and the volume was adjusted to 10mL with ultrapure water, and the metal ion concentration was measured using ICP-MS (Agilent, ICP-MS 7900). The metal ion concentration contained in the hydrogenated nitrile rubber was calculated from the measured value. The metal ions measured at this time were calcium ions, rhodium ions, ruthenium ions, palladium ions, iron ions, sodium ions, and magnesium ions.
[0155] <Bulk density> A piece of approximately 2 cm x 3 cm x 0.2 cm was cut from the hydrogenated nitrile rubber bale and the bulk density (g / cm) was measured using an automatic density meter (manufactured by Toyo Seiki Seisakusho Co., Ltd., product name: "DSG-1"). 3 ) was measured.
[0156] <Stability of conductive material dispersion> The conductive material dispersion obtained in each Example and Comparative Example was measured for viscosity (η0) and then stored in a sealed container at 25°C for 10 days. The dispersion viscosity was then measured again (η1) and the viscosity change rate was calculated according to the following formula, which was used as the conductive material dispersion stability. Evaluation was performed according to the following criteria. Viscosity change rate Δη=η1 / η0×100 A: Viscosity change rate Δη is 80% or more and 120% or less B: Viscosity change rate Δη is 75% or more and less than 80%, or more than 120% and less than 130% C: Viscosity change rate Δη is 70% or more and less than 75%, or more than 130% and less than 140% D: Viscosity change rate Δη is less than 70% or more than 140%
[0157] <Peel strength> The positive electrodes prepared in the examples and comparative examples were cut into a rectangle of length: 100 mm, width: 10 mm to prepare test pieces, and cellophane tape (compliant with JIS Z1522) was attached to the surface of the positive electrode composite layer with the surface having the positive electrode composite layer facing down, and the stress when one end of the current collector was pulled vertically at a pulling speed of 100 mm / min and peeled off was measured (note that the cellophane tape was fixed to the test table). The measurement was performed three times, and the average value was calculated, which was taken as the peel strength and evaluated according to the following criteria. The larger the peel strength value, the stronger the adhesion of the positive electrode composite layer to the current collector made of aluminum foil. A: Peel strength is 25N / m or more B: Peel strength is 20N / m or more and less than 25N / m C: Peel strength is 15N / m or more and less than 20N / m D: Peel strength is less than 15N / m
[0158] Example 1 <Production of hydrogenated nitrile rubber> -Emulsion polymerization process~Washing and drying process- Into a reactor having an internal volume of 10 L, 100 parts of ion-exchanged water, 33 parts of acrylonitrile as an α,β-ethylenically unsaturated nitrile monomer, and 67 parts of 1,3-butadiene as a conjugated diene monomer were charged, and 2 parts of potassium oleate as an emulsifier, 0.1 parts of potassium phosphate as a stabilizer, and further, 0.3 parts of tert-dodecyl mercaptan (TDM) as a molecular weight regulator were added, and emulsion polymerization was carried out at a temperature of 5°C in the presence of 0.35 parts of potassium persulfate as a polymerization initiator, thereby copolymerizing acrylonitrile and 1,3-butadiene. When the polymerization conversion rate reached 89%, 0.2 parts of hydroxylamine sulfate per 100 parts of monomer was added to terminate the polymerization. The mixture was then heated and steam distilled at about 90°C under reduced pressure to recover the residual monomer, and 0.1 parts of dibutylhydroxytoluene (BHT), a phenolic antioxidant, was added to obtain an emulsion polymerization liquid.
[0159] A 25% aqueous solution of calcium chloride (CaCl2) was added as a coagulant in an amount of 3 parts per 100 parts of polymer solids in the obtained emulsion polymerization liquid while stirring, and the polymer in the emulsion polymerization liquid was coagulated. After that, the polymer was filtered, washed with 50 times the amount of ion-exchanged water relative to the obtained polymer, and then dried under reduced pressure at a temperature of 90°C to obtain a polymer.
[0160] -Hydrogenation process I (metase reaction)- Next, 9 parts of the obtained polymer was dissolved in 141 parts of monochlorobenzene and charged into a reactor. Then, after heating the reactor to 80°C, 2L of a monochlorobenzene solution containing bis(tricyclohexylphosphine)benzylidene ruthenium dichloride as a Grubbs catalyst was added so that the amount of Grubbs catalyst relative to the polymer was 1000 ppm. Then, 4.4 parts of cis-2-butene-1,4-diol as a coolefin was added relative to 100 parts of precursor 1, and the polymer was subjected to a metathesis reaction at a stirring speed of 600 rpm. During the reaction, the temperature was kept constant using a cooling coil connected to a temperature control device and a heat sensor.
[0161] -Hydrogenation process II (hydrogenation reaction)- Then, the inside of the reactor was degassed three times with 0.7 MPa H2 while continuing stirring. Then, the temperature of the reactor was raised to 130°C, and 1 L of a monochlorobenzene solution containing Wilkinson's catalyst and triphenylphosphine was added to the reactor. The amount of Wilkinson's catalyst was 0.02 parts and the amount of triphenylphosphine was 1 part per 100 parts of the polymer. Then, the temperature was raised to 138°C, and the hydrogenation reaction of the polymer was carried out under the condition of a hydrogen pressure (gauge pressure) of 8.4 MPa.
[0162] -Purification process- After the hydrogenation reaction was completed, 0.2 parts of activated carbon with an average diameter of 15 μm was added to the reactor and stirred for 30 minutes in order to adjust the concentration of divalent or higher metal ions including calcium ions. Then, the mixture was filtered through a filter with a pore size of 5 μm. The filtrate was then heated and dried until the monochlorobenzene solvent reached 50 ppm, and hydrogenated nitrile rubber A was isolated. The iodine value and metal content were measured using the hydrogenated nitrile rubber A obtained. The results are shown in Table 1. In addition, 20 parts (20 kg) of the isolated nitrile rubber A were filled into a 300×650×300 mm baler and pressed at a pressure of 3 MPa for 30 seconds to obtain nitrile rubber bale A. When the hydrogenated nitrile rubber bale A was measured in the same manner as hydrogenated nitrile rubber A, the measured values were the same.
[0163] <Preparation of positive electrode binder> 920 parts of NMP was weighed out into a 2 L container equipped with a stirring blade and heated to 80° C. Next, 80 parts of hydrogenated nitrile rubber A cut into pieces of about 1 cm square from the hydrogenated nitrile rubber bale A produced above was added and dissolved while continuing to stir for 5 hours to prepare a positive electrode binder A with a solid content concentration of 8%.
[0164] <Preparation of Conductive Dispersion Liquid> Multi-walled carbon nanotubes as conductive materials (BET specific surface area: 250 m 2 5 parts of 1000g / g, 12.5 parts of the positive electrode binder with a solid content concentration of 8% obtained as described above (equivalent to 1 part as solid content), and 82.5 parts of NMP as an organic solvent were added, and the mixture was stirred using a disperser (3000 rpm, 10 minutes), and then mixed for 1 hour at a peripheral speed of 8 m / s using a bead mill (Ashizawa Finetech, "LMZ015") using zirconia beads with a diameter of 1 mm to prepare a conductive material dispersion, and the viscosity was measured. The stability of the conductive material dispersion was evaluated, and the results are shown in Table 1.
[0165] <Preparation of slurry for secondary battery positive electrode> In the above-mentioned conductive material dispersion, a ternary active material having a layered structure (LiNi 0.5 Co 0.2 Mn 0.398.0 parts of 02) (average particle size: 10 μm), 1.0 part of polyvinylidene fluoride as a binder, 1.0 part of the conductive material dispersion (solid content equivalent), and NMP were added and mixed with a planetary mixer (60 rpm, 30 minutes) to prepare a positive electrode slurry. The amount of NMP added was adjusted so that the viscosity of the resulting positive electrode slurry (measured with a single cylindrical rotational viscometer in accordance with JIS Z8803:1991. Temperature: 25°C, rotation speed: 60 rpm) was within the range of 4000 to 5000 mPa·s.
[0166] <Preparation of positive electrode> An aluminum foil having a thickness of 20 μm was prepared as a current collector. The above-mentioned positive electrode slurry was applied to the aluminum foil with a comma coater so that the coating weight after drying was 20 mg / cm. 2 The coating was applied so that the coating would become 1.5 g / cm 2 , and the coating was dried at 120°C for 5 minutes and at 130°C for 5 minutes, and then heat-treated at 60°C for 10 hours to obtain a positive electrode blank. This positive electrode blank was rolled with a roll press to obtain a positive electrode blank with a density of 3.5 g / cm 2 . 3 A sheet-shaped positive electrode was prepared by combining the positive electrode mixture layer and aluminum foil. This sheet-shaped positive electrode was cut to a width of 4.8 cm and a length of 50 cm to prepare a positive electrode for a lithium ion secondary battery. The peel strength of the obtained positive electrode for a lithium ion secondary battery was evaluated.
[0167] Example 2 Except for changing the amount of activated carbon used in the purification step to 0.08 parts, hydrogenated nitrile rubber B, hydrogenated nitrile rubber veil B, and positive electrode binder B were obtained in the same manner as in Example 1. Measurements and performance evaluations of hydrogenated nitrile rubber B were performed, and the results are shown in Table 1.
[0168] Example 3 Except for changing the amount of activated carbon used in the purification step to 0.07 parts, hydrogenated nitrile rubber C, hydrogenated nitrile rubber veil C, and positive electrode binder C were obtained in the same manner as in Example 1. Measurements and performance evaluations of hydrogenated nitrile rubber C were performed, and the results are shown in Table 1.
[0169] Example 4 Except for changing the amount of activated carbon used in the purification step to 0.05 parts, hydrogenated nitrile rubber D, hydrogenated nitrile rubber veil D and positive electrode binder D were obtained in the same manner as in Example 1. Measurements and performance evaluations of hydrogenated nitrile rubber D were performed, and the results are shown in Table 1.
[0170] Example 5 Except for changing the amount of Wilkinson catalyst in the hydrogenation reaction to 0.15 parts, hydrogenated nitrile rubber E, hydrogenated nitrile rubber veil E, and positive electrode binder E were obtained in the same manner as in Example 1. Measurements and performance evaluations of hydrogenated nitrile rubber E were performed, and the results are shown in Table 1.
[0171] Comparative Example 1 Except for changing the amount of Wilkinson catalyst in the hydrogenation reaction to 0.12 parts, hydrogenated nitrile rubber F, hydrogenated nitrile rubber veil F, and positive electrode binder F were obtained in the same manner as in Example 1. Measurements and performance evaluations of hydrogenated nitrile rubber F were performed, and the results are shown in Table 1.
[0172] Comparative Example 2 Except for not carrying out the hydrogenation reaction, a nitrile rubber G was obtained in the same manner as in Example 1. The nitrile rubber G was measured and its performance was evaluated, and the results are shown in Table 1.
[0173] Comparative Example 3 Except for changing the amount of Grubbs catalyst in the metathesis reaction to 200 ppm and the amount of Wilkinson catalyst to 0.03 parts, hydrogenated nitrile rubber H, hydrogenated nitrile rubber veil H and positive electrode binder H were obtained in the same manner as in Example 1. Measurement and performance evaluation of hydrogenated nitrile rubber H were performed, and the results are shown in Table 1.
[0174] Comparative Example 4 Except for changing the amount of Grubbs catalyst in the metathesis reaction to 3000 ppm and the amount of Wilkinson catalyst to 0.03 parts, hydrogenated nitrile rubber I, hydrogenated nitrile rubber veil I, and positive electrode binder I were obtained in the same manner as in Example 1. Measurement and performance evaluation of hydrogenated nitrile rubber I were performed, and the results are shown in Table 1.
[0175] [Table 1]
[0176] It can be seen from Table 1 that the hydrogenated nitrile rubbers A to E of the present invention have a high level of balance between the conductive material dispersion stability and the peel strength of the produced electrodes.
[0177] From Table 1, it can be seen that the peel strength of the electrode is correlated with the iodine value of the hydrogenated nitrile rubber, and that the hydrogenated nitrile rubber with the iodine value that has been conventionally used cannot meet this extremely high electrode peel strength (Comparative Examples 1 to 2).
[0178] It can also be seen from Table 1 that the stability of the conductive material dispersion liquid and the electrode peel strength are inversely related to each other (comparison among Comparative Examples 1 to 4).
[0179] In the present invention, it is found that, in this conflicting relationship, by setting the Ca content of the hydrogenated nitrile rubber within a specific range, the properties of both are highly balanced. Specifically, hydrogenated nitrile rubber with a small iodine value is excellent in the stability of the conductive material dispersion but is poor in peel strength, and it is found that by adding Ca within a specific range, the electrode peel strength can be increased without deteriorating the dispersion stability (Examples 2 to 4).
[0180] (Examples 6 to 10) A large amount of steam was introduced into the hydrogenated nitrile rubber-containing monochlorobenzene solution filtered after the purification steps of Examples 1 to 5 to isolate hydrous crumbs. The isolated hydrous crumbs were then dried under conditions that would not affect the properties of the hydrogenated nitrile rubber using a screw-type extruder having a vacuum drying barrel and a substantially rectangular die section, and a sheet-like dried rubber (width 300 mm x thickness 30 mm) was extruded. After the extruded dried rubber sheet reached 50°C or lower, it was cut to a predetermined length of 650 mm, and 10 sheets were stacked to obtain hydrogenated nitrile rubber bales J to N. When the bulk density of hydrogenated nitrile rubber bales J to N from which the internal air had been removed using the screw-type extruder was measured, the bulk density was 0.85 g / cm. 3This was a value far greater than the bulk density of 0.7 to 0.75 for the hydrogenated nitrile rubber bales A to E compressed at 3 MPa using the balers of Examples 1 to 5.
[0181] Using the hydrogenated nitrile rubber bales J to N thus produced, positive electrode binders J to N were prepared in the same manner as in Examples 1 to 5, and performance evaluation was performed. Although the evaluation level was not changed, all performances were significantly higher than the results of Examples 1 to 5. Furthermore, when the evaluation was performed on an average of five runs, the results were good with little variation. It is presumed that this is because hydrogenated nitrile rubber bales J to N contain less air inside, making it difficult for oxygen radicals to be generated, and preventing the deterioration of each characteristic. Incidentally, when crumb-like hydrogenated nitrile rubbers A to E are obtained by directly drying the water-containing crumbs before being fed into a screw-type extruder, the bulk density of each is 0.5 to 0.6 g / cm. 3 The range was.
[0182] The screw-type extruder used in Examples 6 to 10 was composed of one supply barrel, three dehydration barrels (first to third dehydration barrels), five drying barrels (first to fifth drying barrels) and a die section, and the operating conditions of the screw-type extruder were as follows:
[0183] Set temperature for each barrel: ·1st to 3rd dehydration barrels: 90~120℃ · Drying barrels 1 to 5: 120~180℃ Operating conditions: Diameter of the screw in the barrel unit (D): 132mm Total length of the screw in the barrel unit (L): 4620mm Length / Depth:35 - Rotation speed of the screw in the barrel unit: 135 rpm ·Residence time: 100 seconds Dry barrel vacuum level: 10kPa Die resin pressure: 2MPa
[0184] In addition, the hydrogenated nitrile rubber bales J to N produced above were different from the hydrogenated nitrile rubber bales A to E produced in Examples 1 to 5 in terms of bulk density as a bale characteristic, but the molecular weight, iodine value, antioxidant content and various metal contents of the constituent hydrogenated nitrile rubber were the same. [Industrial Applicability]
[0185] According to the present invention, it is possible to provide a hydrogenated nitrile rubber and a production method thereof, which are excellent in stability of a conductive material dispersion and can achieve high-grade electrode peeling. Furthermore, according to the present invention, it is possible to provide a hydrogenated nitrile rubber veil which has excellent stability in a conductive material dispersion and can achieve high degree of electrode peeling. According to the present invention, it is possible to provide a binder for a positive electrode, which has excellent stability of a conductive material dispersion and can achieve high-grade electrode peeling.
Claims
1. A hydrogenated nitrile rubber containing a nitrile group-containing monomer unit and a conjugated diene monomer unit and / or an alkylene structural unit, having an iodine value of 60 to 120 mg / 100 mg, a weight average molecular weight (Mw) of 1,000 to 1,000,000, and a calcium (Ca) content of 50 to 2,500 ppm.
2. The hydrogenated nitrile rubber according to claim 1, further comprising a phenol-based antioxidant.
3. The hydrogenated nitrile rubber according to claim 2, wherein the content of the phenol-based antioxidant is in the range of 0.001 to 2 mass %.
4. The hydrogenated nitrile rubber according to claim 1, further comprising a palladium (Pd) content of 50 ppm or less.
5. The hydrogenated nitrile rubber according to claim 1, further comprising a magnesium (Mg) content of 50 ppm or less.
6. The hydrogenated nitrile rubber according to claim 1, further comprising a sodium (Na) content of 300 ppm or less.
7. Bulk density is 0.8 g / cm 3 The hydrogenated nitrile rubber according to claim 1.
8. The hydrogenated nitrile rubber according to claim 7, wherein the total ratio of the nitrile group-containing monomer units and the conjugated diene monomer units and / or alkylene structural units in the hydrogenated nitrile rubber is 95 mass% or more.
9. The method for producing hydrogenated nitrile rubber according to any one of claims 1 to 8, comprising a step of emulsion-polymerizing a monomer component containing a nitrile group-containing monomer and a conjugated diene monomer, coagulating the polymer obtained by polymerization with calcium chloride, and hydrogenating the polymer with a rhodium-based catalyst and / or a ruthenium-based catalyst.
10. The method for producing hydrogenated nitrile rubber according to claim 9, wherein the hydrogenated nitrile rubber after the hydrogenation is dried using a screw-type extruder.
11. The method for producing hydrogenated nitrile rubber according to claim 10, wherein the screw-type extruder has a drying barrel under reduced pressure.
12. A hydrogenated nitrile rubber bale obtained by baling the hydrogenated nitrile rubber according to any one of claims 1 to 8.
13. A binder for a positive electrode, comprising the hydrogenated nitrile rubber according to any one of claims 1 to 8 dispersed or dissolved in N-methylpyrrolidone (NMP).
Citation Information
Patent Citations
Binder composition for nonaqueous secondary battery positive electrode, composition for nonaqueous secondary battery positive electrode, positive electrode for nonaqueous secondary battery, and nonaqueous secondary battery
JP2018160421A
Binder composition for electrochemical elements, conductive material dispersion for electrochemical elements, slurry for electrodes for electrochemical elements, electrodes for electrochemical elements, and electrochemical elements
JP6870772B1
Dispersant composition for electrochemical elements, conductive material dispersion for electrochemical elements, slurry composition for electrochemical element electrodes and method for producing the same, electrodes for electrochemical elements, and electrochemical elements
JP6911985B1
Binder composition for non-aqueous secondary cell positive electrode, composition for non-aqueous secondary cell positive electrode, non-aqueous secondary cell positive electrode and non-aqueous secondary cell, and method for producing composition for non-aqueous secondary cell positive electrode, non-aqueous secondary cell positive electrode and non-aqueous secondary cell
WO2016103730A1